2014
DOI: 10.1002/cphc.201300857
|View full text |Cite
|
Sign up to set email alerts
|

Heteronuclear Cross‐Relaxation Effects in the NMR Spectroscopy of Hyperpolarized Targets

Abstract: Dissolution DNP enables high-sensitivity solution phase NMR experiments on long-lived nuclear spin species such as 15 N and 13 C. This report explores certain features arising in solution-state 1 H NMR, upon polarizing low-γ nuclear species. Following solid state hyperpolarization of both 13 C and 1 H, solution-phase 1 H NMR experiments on dissolved samples revealed transient effects whereby peaks arising from protons bonded to the naturally-occurring 13 C nuclei, appeared larger than the typically dominant 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…36,37,41,45,58,59 In an effort to explain these features we first examined the three spin system { 1 H-e-13 C} and simulated DNP spectra using the ''double-SE'' mechanism, as described by de Boer. DNP on heteronuclear spin systems often results in interesting phenomenon such as the polarization enhancement of one nucleus during MW irradiation at the ''forbidden'' transition frequencies of another nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37,41,45,58,59 In an effort to explain these features we first examined the three spin system { 1 H-e-13 C} and simulated DNP spectra using the ''double-SE'' mechanism, as described by de Boer. DNP on heteronuclear spin systems often results in interesting phenomenon such as the polarization enhancement of one nucleus during MW irradiation at the ''forbidden'' transition frequencies of another nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…This formalism predicts that all nuclei in the sample reach the same nuclear spin temperature, which also means that their enhancements at each MW frequency are equal and thus their DNP spectra become the same. 41,45,58,59 In the present paper we present 13 C-DNP experiments on samples containing trityl radicals that also result in DNP spectra with extra spectral features outside of the EPR frequency range. These positive and negative enhancements were not explained by the DNP mechanisms mentioned above.…”
Section: Introductionmentioning
confidence: 98%
“…It is worth noticing that these observations are reminiscent of previous works related to solid samples at low temperatures [15][16][17][18] in some cases enhanced by DNP [19][20][21] . Moreover, Donovan et al 22 have shown that rapid hetero-nuclear cross-relaxation could lead to significant transfer. This is a case where the use of SPY-MR cannot be recommended.…”
Section: Introductionmentioning
confidence: 98%
“…This is suitable for many heteronuclear spins, such as non‐protonated 13 C spins, which have relaxation rates of several 10's of seconds. Such transfer times, however, are not compatible with the direct DNP enhancement of 1 H signals – although cross‐relaxation processes form slow‐relaxing nuclei may still yield significant 1 H enhancements . Using fast transfer and injection devices, hyperpolarised 1 H experiments can be carried out, and a broader range of signals are observed for heteronuclei …”
Section: Dissolution Dynamic Nuclear Polarisationmentioning
confidence: 99%
“…Such transfer times, however, are not compatible with the direct DNP enhancement of 1 H signalsalthough cross-relaxation processes form slow-relaxing nuclei may still yield significant 1 H enhancements. [14] Using fast transfer and injection devices, hyperpolarised 1 H experiments can be carried out, and a broader range of signals are observed for heteronuclei. [15] The harsh conditions of the dissolution and transfer step make the analysis of biomacromolecules by D-DNP challenging, as they may not recover their conformation of interest post dissolution.…”
Section: Samplesmentioning
confidence: 99%